Research Methodology Design for WBAN Smart System Connection to Control Covide19 Patients Remotely - Israa Al_barazanchi; Haider Rasheed Abdulshaheed; Wahidah Hashim; Ammar Ahmed Alkahtani; Rina Azlin Razali; Elika daghighi; Zahraa A. Jaaz; Shihab A. Shawkat (Journal of Telecommunication Control and Intelligent System, 2021)
The main objective of any research is to find a solution that helps solve a certain problem or improve the performance of the current solution. Therefore, sufficient justification of the study should be presented as there must be a specific problem to try to resolve it. The second objective is to prove that the research methodology developed as a proposal to solve the problem, and which is expected to achieve the results with the participation of an active contribution in this field There are two types of research methodology available, the stander and specific. The stander methodology includes the V-Shaped methodology, Design Research Methodology (DRM), and spiral methodology; Therefore, the research methodology used by this research will be scientific and relevant to cover the scientific aspects from the beginning of the work to the end. The proposed smart system will be tested using the simulation environment and will be validated by comparing the results obtained with the existing research to prove the proposed smart system called as IKS is able to increase the network performance in WBAN. The analysis of the network performance was implemented in real WBAN dataset and used the Multi-Parameter Intelligent Monitoring for Intensive Care (MIMIC) database. MIMIC database included the data recorded from 90 Intensive Care Unit (ICU) patients